EASY WAY OF SHOPPING ONLINE WITH A CREDIT CARD AND CASH IN ON THE GLODOK SHOP - Wahyuningsih Wahyuningsih; Sahni Damerianta Purba, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Glodok Shop is an electronics store that uses the internet as a medium distance services. transaction services provided is very easy, fast and secure for potential buyers. prospective buyers do not have to leave home to shop, anytime and from anywhere. Payment methods offered can be through credit cards and cash at the place / COD (Cash On Delevery). but this shopping system is less accepted by society, because there are many who doubt the ease and quality of product sales. With the increase of services provided, it is possible that this online shopping system will be more accepted by society at large.